2013
DOI: 10.1542/peds.2013-1488
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Physical Activity, Sedentary Behavior, Diet, and BMI Among US Adolescents, 2001–2009

Abstract: WHAT'S KNOWN ON THIS SUBJECT:The prevalence of overweight and obesity in US adolescents has increased over the last century. However, recent evidence indicates a potential change in this trend. Parallel trends in adolescent behaviors that drive this epidemic have not been well studied. WHAT THIS STUDY ADDS:Analyses of recent data indicate the prevalence of overweight and obesity may be stabilizing. Over the same period, adolescent physical activity, breakfast eating, and fruit and vegetable consumption increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
119
4
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(149 citation statements)
references
References 37 publications
(41 reference statements)
23
119
4
3
Order By: Relevance
“…After years of steady increase, obesity rates have finally begun to level off (7,10). Overall, children are consuming fewer calories today than they did a decade ago, and fewer of their calories are coming from carbohydrates (8,9). The consumption of fast food has also declined (25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After years of steady increase, obesity rates have finally begun to level off (7,10). Overall, children are consuming fewer calories today than they did a decade ago, and fewer of their calories are coming from carbohydrates (8,9). The consumption of fast food has also declined (25).…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of fast food has also declined (25). Children are also more physically active than they were a decade ago (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A very recent study showed significant increases in daily physical activities and consumption of fruits and vegetables between 2001 and 2010 in a nationally representative cohort of students in grades 6 to 10. Television viewing and the consumption of sweets and sweetened beverages decreased during the same time period [26].…”
Section: Possible Causes and Consequences Of The Observed Trends In Cmentioning
confidence: 94%
“…However, the factors that explain the increase in the number of obese children appear to be specifically related to lifestyle changes 9,10 . According to the literature, an obesity epidemic in youth appears to be the result of changes in modern society.…”
Section: Introductionmentioning
confidence: 99%